Case Report: Mycoplasma pneumoniae-induced rash and mucositis (MIRM) in an 8-year-old girl: concise review of a challenging case. - Li, Yun-Long; Wang, He-Wen (Frontiers in Pediatrics, 2025)
We report an 8-year-old girl presenting with an 8-day history of cough, 5-day fever, and recent-onset conjunctival hyperemia and oral mucosal erosions. Laboratory testing confirmed Mycoplasma pneumoniae infection (IgM antibody and DNA positive). Chest x-ray demonstrated bilateral increased and blurred lung markings, consistent with acute bronchitis. Initial treatment with azithromycin and methylprednisolone sodium succinate (MPSS) improved respiratory symptoms but triggered a progressive rash involving the trunk, perineum, and anus. Adjuvant therapy with intravenous immunoglobulin (IVIG, 22.5 g) and continued immunomodulation with MPSS led to resolution of mucocutaneous manifestations by hospital day 10. This case highlights the potential for M. pneumoniae to induce systemic immune-mediated reactions and underscores the importance of multimodal therapy.